(untitled) (European Journal of Economics, Finance and Business Development, 2024)
This article explores the significance of effective risk forecasting in financial relations among business entities. It delves into current methodologies, their limitations, and proposes innovative approaches for more accurate risk assessment. By synthesizing existing literature and proposing novel methods, this article aims to contribute to the advancement of risk management practices in the realm of business finance.